Analisis Studi Literatur Penerapan Algoritma Pemrograman pada Internet of Things (IoT) - Muhammad Murdani; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
By using literature studies/literature research, this article discusses how programming algorithms can be applied to the Internet of Things (IoT). The purpose of this article is to explain the function of algorithms in Internet of Things (IoT) programming and several examples. IoT is a concept where various devices and objects can connect and communicate with each other via the internet network. After data is collected through text study, content analysis techniques are used to analyze it. Literature studies show that programming algorithms must be applied to the Internet of Things to ensure efficient collection, analysis and use of data from connected objects. Programming algorithms are widely used for data prediction and analysis, network management, data collection and processing, security, and optimization of communication between IoT objects. Internet of Things developers and researchers should pay attention to the importance of implementing appropriate programming algorithms in their systems because these algorithms enable IoT to optimize the use of resources such as bandwidth, memory, and energy. Efficient algorithms enable smarter data analysis and better data security.